Analysis of Students' Critical Thinking Ability Profile Using HOTS-Based Questions - M. Noris; Misbahul Jannah; Margiyono Suyitno; Setria Utama Rizal (Postgraduate, University of Mataram, 2024)
Critical thinking includes higher processes, such as analysis, synthesis, evaluation, conclusion, and reflection. This research aims to determine the profile level of students' critical thinking abilities. The research sample consisted of 28 students taken by random sampling consisting of 2 classes. Data was obtained through test and non-test techniques which included a critical thinking ability test using 20 questions. Meanwhile, the non-test uses an observation sheet on students' critical thinking abilities. Analysis of data obtained from the results of students' critical thinking skills tests was then analyzed using analysis items with the Rasch model. The results of the profile analysis of students' critical thinking skills were classified as moderate. This is proven by test results and observations in basic biology courses. Based on the results of tests on students' critical thinking skills, it is known that there are 16 students who have high levels of critical thinking skills, 5 students with moderate critical thinking skills, and 6 students with weak critical thinking skills. Meanwhile, the results of observations of the critical thinking abilities of Bima Muhammadiyah University students in basic biology courses are in the moderate critical thinking ability category with a category score of around 68.06%.